Pica for Uncooked Basmati Rice in Two Women with Iron Deficiency and a Review of Ryzophagia - James C. Barton; J. Clayborn Barton; Luigi F. Bertoli (Case Reports in Medicine)
Reports of pica for uncooked rice (ryzophagia) in adults who reside in European and derivative countries are uncommon. We evaluated and treated two nonpregnant women with pica for uncooked basmati rice. Both women reported fatigue, abdominal discomfort after consuming large quantities of uncooked basmati rice, and hair loss. One woman was from India and the other was from Pakistan. Both women were vegetarians. Basmati was the local rice in their native countries and their usual rice in the USA. Both women had tooth damage due to eating uncooked rice and iron deficiency with microcytic anemia attributed to menorrhagia and multiparity. Ryzophagia and other manifestations (except tooth damage) resolved after iron dextran therapy. We review and discuss other reports of ryzophagia associated with iron deficiency, pregnancy, race/ethnicity, geographic origin, and local traditions. We conclude that adults with ryzophagia in European and derivative countries are likely to be non-Europeans.